PERANCANGAN SISTEM QR CODE UNTUK PEMESANAN MENU MAKANAN OTOMATIS PADA KAFE DI BINTARO, TANGERANG SELATAN - Fernando, Jason; Marlon Brando Layanto; Wilson Wiranata; Endah Setyaningsih (Jurnal Serina Abdimas, 2025)
The application of digitalization in the era of industry 4.0 is growing rapidly. Ayoola Coffee & Eatery, one of the MSMEs in the Bintaro area, Tangerang, is experiencing problems in the digitalization of food and beverage ordering. Ayoola Coffee & Eatery is an MSME founded by Mrs. Dewi Irfan in Bintaro, South Tangerang. This business combines the concept of a cafe and art gallery, providing food, drinks, and space for local artists to sell their work. The vision and mission of the partners are to open up employment opportunities for lower-class people to be more prosperous, as well as provide opportunities for them to develop their skills. Currently, these orders can only be made through the cashier, resulting in long queues when busy. This Community Service aims to overcome this problem by implementing a digital system using through the use of QR codes, so that customers can order directly from the table without having to queue. The solutions designed include the development of a website application that displays the menu and allows online ordering, integrated with the Moka Point of Sale (POS) system via API. This system is expected to improve operational efficiency, speed up service, and provide a better customer experience. Through the digitalization of this system, customers can scan the QR code on each table to access the menu, order, and make payments. This implementation also allows MSMEs to optimize inventory management, speed up transactions, and improve the accuracy of sales reporting. The implementation method involves the application of Moka POS to help MSMEs face challenges in the digital era and increase their competitiveness through service digitalization. Based on the results obtained, it is known that the automatic ordering system works according to the desired function. ABSTRAK Penerapan digitalisasi pada era industri 4.0 berkembang pesat. Ayoola Coffee & Eatery, salah satu UMKM di daerah Bintaro, Tangerang, sedang mengalami masalah dalam digitalisasi pemesanan makanan dan minuman ini. Ayoola Coffee & Eatery adalah UMKM yang didirikan oleh Ibu Dewi Irfan di Bintaro, Tangerang Selatan. Usaha ini menggabungkan konsep kafe dan galeri seni, menyediakan makanan, minuman, dan ruang bagi seniman lokal untuk menjual karya mereka. Visi-misi mitra adalah membuka lapangan kerja bagi masyarakat kelas bawah agar lebih sejahtera, serta memberikan kesempatan bagi mereka untuk mengembangkan keterampilan. Saat ini, pemesanan tersebut hanya dapat dilakukan melalui kasir, sehingga menyebabkan antrian panjang saat ramai. Kegiatan Pengabdian Kepada Masyarakat ini bertujuan untuk mengatasi masalah tersebut dengan menerapkan sistem digital melalui penggunaan QR code, sehingga pelanggan dapat memesan langsung dari meja tanpa harus mengantri. Solusi yang dirancang meliputi pengembangan aplikasi website yang menampilkan menu dan memungkinkan pemesanan online, terintegrasi dengan sistem Point of Sale (POS) Moka melalui API. Sistem ini diharapkan meningkatkan efisiensi operasional, mempercepat layanan, dan memberikan pengalaman pelanggan yang lebih baik. Melalui digitalisasi sistem ini Pelanggan dapat memindai QR code di setiap meja untuk mengakses menu, memesan, dan melakukan pembayaran. Implementasi ini juga memungkinkan UMKM untuk mengoptimalkan manajemen inventaris, mempercepat transaksi, serta meningkatkan akurasi pelaporan penjualan. Metode pelaksanaan melibatkan penerapan Moka POS untuk membantu UMKM dalam menghadapi tantangan di era digital dan meningkatkan daya saing mereka melalui digitalisasi pelayanan. Berdasarkan hasil yang didapat diketahui bahwa sistem pemesanan otomatis bekerja sesuai fungsi yang ingin dicapai.